Internalisasi Akhlak dalam Kajian kitab Ar-Risalah Al-Maimunah (Studi Fenomenologi di STAI Attanwir Bojonegoro) - Asnawi Asnawi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
The fact that the Kitab Ar-Risalah Al-Maimuniyah is one of the mandatory courses in the Islamic Guidance and Counseling Study Program at STAI At-Tanwir Bojonegoro highlights the importance of a deep understanding of how students respond to, comprehend, and implement the teachings of ethics and morality in their daily lives. Therefore, the objective of this research is the Internalization of Morality in the Study of the Kitab Ar-Risalah Al-Maimunah. The research method employed is qualitative using a phenomenological approach. Data collection methods are focused on in-depth interviews. The data analysis technique utilized is the Phenomenological technique. The findings of this research include a portrayal of the Internalization of Morality in the Study of the Kitab Ar-Risalah Al-Maimunah, which encompasses (1) Deep Understanding: Research subjects have a profound understanding of the moral values contained within the Kitab, (2) Application in Life: Subjects are able to implement these moral values in their daily lives, both academically and socially. They may take tangible actions based on the teachings they have learned from the Kitab, (3) Personal Growth: The process of internalizing moral values from the Kitab has had a significant impact on the personal growth of the subjects, and (4) Environmental Influence: Findings also encompass how the academic environment at STAI Attanwir Bojonegoro influences the process of moral internalization of the research subjects. Factors such as interaction with lecturers and fellow students can also play a role in shaping the character and moral values of the subjects.